(untitled) (Fiep Bulletin - online, 2014)
The absences from work from sickness have increased considerably in recent years in Brazil and among the main causes are musculoskeletal injuries. This study is an investigation of the occurrence of pain in metallurgical industry workers in the State of Paraná. Was used initially the Nordic Musculoskeletal Questionnaire (NMQ) for the identification of symptoms of musculoskeletal pain and/or discomfort. Was also used the methodology Rapid Upper Limb Assessment (RULA) for ergonomic evaluation and diagnostics of movement adopted by the workers. It identifies postures and proposes improvements and adaptations to the activities performed. Overall it was realized that the musculoskeletal requirements are originated by the inadequacy of machinery and equipment used to perform the tasks, causing inadequate movements with high physical demands, causing pain and possibly evolving into musculoskeletal injuries.